Effect of sintering temperature on sensitivity of MgB4O7:Tm, Ag obtained by the solution combustion method. (January 2021) - González, P.R.; Ávila, O.; Mendoza-Anaya, D.; Escobar-Alarcón, L.
Abstract: Borates are appropriate TL materials for radiation dosimetry, because of their equivalence with tissue. Magnesium borate is a tissue equivalent material and its most important advantage over lithium borate, is that this material is insoluble in water. In this work the effect of sintering temperature on the sensitivity of magnesium borate obtained by the solution combustion technique is presented. The results showed that the material doped with Tm and Ag, subjected to 1223 K, for 3 h, had a sensitivity between two and four times higher than that of the commercial dosimeter TLD-100 making it highly appropriate for applications in clinical dosimetry. Highlights: Magnesium borate was obtained by the combustion method. Effect of thermal treatment on the TL response was studied. Effect of concentration of dopant was studied. The effect of thermal treatment on the glow curve was studied.